Behavior and Health Promotion in an Effort to Reduce Morbidity and Mortality Among Children Under Five - Joaquim Pinto; Joaquim Gregorio de Carvalho; Ermelinda da Costa Monteiro; Carlos Boavida Tilman (Medical Studies and Health Journal (SEHAT), 2024)
Health behavior and promotion are key factors in reducing morbidity and mortality in children under five years of age, which remains a significant challenge worldwide. Factors such as stunting, malnutrition, acute respiratory infections (ARI), diarrhea, and pneumonia contribute to this problem. This study aims to explore the role of parental involvement in community-based health promotion programs in reducing morbidity and mortality in children under five years. The method used is a systematic literature review with the PRISMA approach, identifying and analyzing articles from reputable international databases. Findings show that parental involvement can significantly increase the effectiveness of health programs, with a positive impact on reducing child morbidity and mortality rates. The implications of this research emphasize the need for policies that support community-based prevention programs, integration of health strategies with parental involvement, and increased awareness of the role of parents in children's health.